Minimally Invasive Glaucoma Surgery—A Comprehensive Review - Devendra Maheshwari; Harinikrishna Balakrishnan; Mohideen A. Kader; Ramakrishnan Rengappa (TNOA Journal of Ophthalmic Science and Research, 2025)
Glaucoma is a progressive and irreversible optic neuropathy that can lead to blindness if left untreated, with intraocular pressure (IOP) being the primary modifiable risk factor. Minimally invasive glaucoma surgery (MIGS) refers to a set of procedures designed to lower IOP with minimal disruption to normal eye anatomy, offering a high level of safety, efficacy and fast recovery. While glaucoma is initially treated with medications, patients who do not respond to medical or laser treatments often require surgical intervention. Traditional surgeries like trabeculectomy and tube shunts, although effective, carry higher risks and complications. MIGS provides a safer alternative, offering shorter recovery times and effective IOP reduction, particularly for patients with mild-to-moderate glaucoma who are either non-compliant with or intolerant to medications. MIGS procedures lower IOP by enhancing aqueous humour outflow through trabecular, scleral or uveoscleral pathways or by reducing aqueous production via ciliary body ablation. Some common MIGS devices include the iStent, Hydrus Microstent, Kahook Dual Blade and CyPass, each targeting different outflow mechanisms. While MIGS offers promising results in reducing IOP and medication dependency, they do come with some risks, such as transient hyphema and IOP spikes after surgery. This review outlines the mechanisms, types, outcomes and limitations of MIGS, providing valuable insights for clinicians managing glaucoma, especially for those considering alternatives to traditional filtration surgeries.